2021
DOI: 10.3389/fphar.2021.796590
|View full text |Cite
|
Sign up to set email alerts
|

Diammonium Glycyrrhizinate Ameliorates Obesity Through Modulation of Gut Microbiota-Conjugated BAs-FXR Signaling

Abstract: Obesity is a worldwide epidemic metabolic disease. Gut microbiota dysbiosis and bile acids (BAs) metabolism disorder are closely related to obesity. Farnesoid X-activated receptor (FXR), served as a link between gut microbiota and BAs, is involved in maintaining metabolic homeostasis and regulating glucose and lipid metabolism. We previously reported that diammonium glycyrrhizinate (DG) could alter gut microbiota and prevent non-alcoholic fatty liver disease. However, it remains ambiguous how DG affects the gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…However, this hypothesis is in contrast with the assumption of FXR activation being beneficial during NAFLD [ 69 ]. Thus, intestinal FXR antagonists are considered for the treatment of metabolic diseases: the glycine-beta-muricholic acid (namely, a tauro-beta-muricholic acid derivative) is used in experimental models of NAFLD, producing a reduction in obesity, insulin resistance, and liver fibrosis/inflammation grading [ 70 , 71 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, this hypothesis is in contrast with the assumption of FXR activation being beneficial during NAFLD [ 69 ]. Thus, intestinal FXR antagonists are considered for the treatment of metabolic diseases: the glycine-beta-muricholic acid (namely, a tauro-beta-muricholic acid derivative) is used in experimental models of NAFLD, producing a reduction in obesity, insulin resistance, and liver fibrosis/inflammation grading [ 70 , 71 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…PBAs appear to play a role in preventing the development of atherosclerosis through activation of the farnesoid X receptor (FXR) signaling cascade, which improves lipid profile and regulates gluconeogenesis and intestinal barrier function [14]. In addition, PBAs inhibit the NF-kB-dependent activation of Takeda-G protein 5 receptors (TGR5), resulting in a decreased production of proinflammatory cytokines [10,15].…”
Section: Bile Acids Modulation and Cholesterol Metabolismmentioning
confidence: 99%
“…At a later stage, the pancreatic β-cells cannot compensate for the high demand of insulin; therefore, this eventually leads to β-cell dysfunction and defect in insulin secretion, and hyperglycemia occurs [ 58 ]. Studies have shown that GL, GA, and DG could improve insulin sensitivity in diabetic rodents [ 28 , 30 , 31 , 33 , 54 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ].…”
Section: Anti-diabetic Mechanisms Of Gl and Its Derivatives In T2dmmentioning
confidence: 99%
“…Moreover, it also reduced the adipocyte size and area in the subcutaneous WAT of rats [ 65 , 68 ]. Similarly, GL and DG could reduce the weights of WAT in HFD-induced obese rodents [ 30 , 61 ]. Furthermore, peroxisome proliferator-activated receptor-γ (PPAR-γ) is a nuclear receptor, which is highly expressed in adipose tissue [ 76 ].…”
Section: Anti-diabetic Mechanisms Of Gl and Its Derivatives In T2dmmentioning
confidence: 99%